Realtà e narrazione della remissione della scomunica duecentesca nella memoria delle città ghibelline di Toscana: Siena fra XII e XIII secolo - Pellegrini, Michele (Quaderni di storia religiosa medievale, 2022)
In the experience of the Ghibelline cities in Tuscany, the most important aspects of the excommunications to which they were subjected in the context of the political conflict in the early 13th century are the forms in which their remission was celebrated and commemorated. This memory, reworked for centuries in chronicles or hagiographic texts, left a deep mark on the perception of the past and the collective identity of these communities. Focusing attention on Siena and on the hagiographic dossier concerning Blessed Ambrogio Sansedoni, some observations are offered on the effects produced by this memory in the elaboration of the collective identity of the urban community.